Myxoid pleomorphic sarcoma in a non-healing ulcer post-burn of the left foot: A rare case report - Patel, Akhilesh Kumar; Gujar, Sunil; Gurwani, Siddhart; Gupta, Raunak Kumar; Shinde, Siddharth; Ninama, Sneha; Gupta, Rohan; Rathore, Nakul Kumar (Indian Journal of Case Reports, 2020)
Myxoid pleomorphic sarcoma is categorized as a soft-tissue sarcoma that most commonly appears in the lower extremities during adulthood, but rarely in the feet. We present a rare case of a primary myxoid pleomorphic sarcoma in the foot of a 45-year-old female which was rare in females. On examination, a ulceroproliferative growth of around 10 cm × 12 cm size was seen over the posterior aspect of foot involving the whole ankle region, with a thickened scar over the plantar and medial aspect of the right foot. Magnetic resonance imaging of the mass revealed a high signal intensity on T1-weighted images and heterogeneously high signal intensity on T2-weighted images without fat suppression. Histology showed variable cellularity, myxoid granular to the filamentous background, and round to spindled tumor cells. The immunohistochemistry showed positive for vimentin, acid mucins, CD34, and negative for S100. Hence, these findings were consistent with myxoid pleomorphic sarcoma. The patient was treated with below-knee amputation.